HUBUNGAN DAN PENGARUH FAKTOR-FAKTOR RISIKO RANTAI PASOK MATERIAL TERHADAP KINERJA PROYEK PEMBANGUNAN GEDUNG DI KABUPATEN PIDIE JAYA DAN BIREUEN - Fahmi M. Hasan; Mochammad Afifuddin; Abdullah Abdullah (Prodi Magister Teknik Sipil Unsyiah, 2019)
The disaster of an earthquake measuring 6.4 on the Richter Scale (SR) that hit Pidie, Pidie Jaya and Bireuen Districts on December 7, 2016 has resulted in damage to infrastructure and facilities. In an effort to accelerate post-disaster rehabilitation and reconstruction, the Ministry of Public Works and Public Housing, carried out the rebuilding of the At-Taqarrub Mosque, Ulee Glee Market in Pidie Jaya District and Al-Aziziyah Islamic College in Bireuen District. Some of the risks that occur in the implementation of the project are the replacement of material use, the late submission of material proposals from the executor, material fabrication far from the project location, the disruption of land traffic to the project location, instructions for accelerating work so the building is functional before the contract ends from the owner. and there are limitations to suppliers in meeting a large demand for material in a short time. This study aims to analyze the level of relationship and the form of influence between material supply chain risk on project performance. This study uses a combined method, which combines qualitative and quantitative approaches through questionnaires. Respondents were directed at 20 planning personnel, 26 implementing personnel, 6 construction management personnel and 13 owner staff. The independent variables reviewed are supply, control, process and demand factors, while the dependent variable is project performance. The results showed that all material supply chain risk factors had a high relation to project performance. All material supply chain risk factors have a significant effect on project performance, which is equal to 78.8%. The material supply chain risk factor that predominantly affects project performance is the demand factor, with a regression coefficient of 0.283. This means that if the demand factor is handled properly by the executor and the owner, the project performance will increase by 28.3%.